DEVELOPMENT OF A TECHNOLOGICAL SCHEME FOR EXTRACTING THE RHENIUM (III) ION FROM INDUSTRIAL WASTE USING THE ORGANIC REAGENT BISMUTOL-2 - Mirzakhmedov Rustamjon Mirkhamidovich; Mirusmanova Farangis Babur's Qizi (Scholar Express Journal, 2023)
the selection of new organic reagents for the determination of rhenium (III) ions, the levels and optimal conditions of immobilization to various types of sorbents were determined, finding the mechanism of immobilization of the bismutol-2 Reagent to the carrier, as well as determining the optimal conditions for their formation of a complex with the rhenium (III) ion, and applying the developed.
Keywords: Rhenium; ions; bismutol-2